A Comparative Analysis of the Implementation of Regional Head Elections in Mojokerto Regency and Kuantan Singingi Regency - Kencana Asmanto; Ataya Qonita Ananta; Virani Nabillah Putri; Iradhad Sihidi; Ach. Romadhan (Journal of Government Insight, 2026)
This study examines the implementation of the Regional Head Election (Pilkada) in Mojokerto Regency, East Java, and Kuantan Singingi Regency, Riau. This study uses a comparative method with a descriptive qualitative approach. The focus of the study includes the level of public participation, the quality of the election implementation, and the effectiveness of the election implementation. The results of the analysis show significant differences, especially in terms of political participation patterns where Mojokerto Regency shows a very consistent increasing trend from 60% (2015) to 86.67% (2024), an increase of 26.67 percentage points and exceeding the national average. Meanwhile, Kuantan Singingi Regency experiences fluctuations with a "V" pattern, starting from 73.85% (2015), decreasing to 67.41% (2020) due to the impact of the COVID-19 pandemic, then recovering to 76.76% (2024). In terms of effectiveness, Mojokerto Regency shows higher Pilkada effectiveness due to the support of favorable geographical conditions, strong economic stability, and solid institutions. Meanwhile, Kuantan Singingi Regency faces significant challenges in all three areas that hamper the effectiveness of the regional elections. Difficult geographic conditions, compounded by economic constraints and institutional weaknesses, create complex challenges. Thus, this study underscores that the effectiveness of regional elections is not solely determined by national institutional design but also depends heavily on local preparedness, encompassing geography, economic capacity, and the quality of inter-institutional interactions